Covid 19: Consequential Effects on Insurance Industry, Risk Management and Insurability of Pandemic Risk - Shafau, SAKA, Toyin; Johncally, ABERE, Omotayo (International Journal on Orange Technologies, 2022)
The continuous fall in the world economy has a result of the COVID–19 epidemic attracted the interest of many researchers. The pandemic brought about a sharp decline in insurance business and economic growth of the nation; this warranted the closure of many businesses and the insurance businesses is not spared. The objective of this paper is to ascertain the effect of Covid 19 on the insurance business and to determine the most efficient risk management strategies that can coup the effect of the Covid 19 pandemic. Both secondary and primary data was used for this study. Regression model was employed to test the hypotheses raised in this paper. This paper revealed that Covid 19 has significant negative effect on the business operation of insurance businesses in Nigeria. Arisen from the analysis of the study, the paper recommended that: insurance industry should employ effective risk management strategy; there is urgent need for insurance industries to re-strategies their business operation by introducing new products and services; and insurance companies should introduce attractive prices through price reduction and engage fully the e-marketing system.